Предмет: Математика, автор: zxcdelta

100 баллов
пожалуйста быстрее​

Приложения:

Ответы

Автор ответа: iramazurk
0

Пошаговое объяснение:

1

{15 - х = 2у

{4х - 3у = 27

{-х - 2у = -15 | * -1

{4х - 3у = 27

{х + 2у = 15

{4х - 3у = 27

{х = 15 - 2у

{4х - 3у = 27

1)

4х - 3у = 27

4(15 - 2у) - 3у = 27

60 - 8у - 3у = 27

-8у - 3у = 27 - 60

-11у = -33

у = -33 : (-11)

у = 3

2)

х = 15 - 2у

х = 15 - 2 * 3

х = 15 - 6

х = 9

(9; 3)

2

5х - 2у = 9

5х = 9 + 2у

х = (9 + 2у)/5

Похожие вопросы
Предмет: Алгебра, автор: feoktistovadiana500